Analysis of Co-Channel Interference in Connected Vehicles WLAN with UAV. (31st January 2022) - Wang, Maolin; Ma, Xu; Wang, Zhi; Guo, Yang
Abstract : Unmanned aerial vehicle (UAV) has the advantages of flexibility, strong controllability, and easy deployment. It provides wireless communication with low delay and high throughput. However, under the background of the increasing shortage of spectrum resources, the frequency band resources of UAV systems are tight, resulting in increasingly serious co-channel interference between services, and the communication quality cannot be effectively guaranteed. Therefore, it is very important to evaluate the co-channel interference of UAV system and improve its spectral efficiency. This paper introduces the interference model for the research and analysis of the frequent coexistence of UAV and connected vehicles WLAN system and applies the model to evaluate the co-channel interference of UAV in the ISM frequency band of 2.4 GHz. The actual receiver filter is modeled and analyzed, the FDR mathematical expression for changing the protection band is derived, and two UAV interference signal waveforms, cyclic prefix orthogonal frequency division multiplexing waveform and windowed orthogonal frequency division multiplexing waveform, are proposed to effectively improve the utilization of frequency resources. After simulation, the interference of the interfered connected vehicles WLAN system is calculated and compared with the relevant service interference threshold standards issued by the International Telecommunication Union. To ensure that the UAV will not interfere with the connected vehicles WLAN system in the ISM frequency band of 2.4 GHz, the protection height of the UAV system in China is 6.2 km.